An Analysis of Linguistic Errors Made by EFL’s Adult Learners in Translating English into Indonesian language - Julian Chandra; Irna Wahyuni (Fakultas Sastra Universitas Ekasakti, 2019)
The study was aimed at describing what linguistic errors namely, grammatical, syntactical, morphological, phnological and lexical errors that English education program students made in translating Indonesian language into English. This research was a descriptive qualitative research. Research participants were 19 sixth semester students of English education at STKIP YDB who took translation subject for academic year of 2018/2019. The research instrument was translation test derived from the students’ translation midterm examination which comprised translating 15 Indonesian sentences into English. Data was analyzed through error analysis in which was proposed by Ellis (1997) involving steps such as (1) collecting samples / data, (2) identifying the errors, (3) classifying translation errors, (4) explaining the errors, and (5) evaluating / interpreting the error. The results of the study revealed that the main linguistic errors that the students had in translating Bahasa Indonesia into English was in lexical aspect. It was found that lexical error comprised 72,8% of total errors. For grammar and syntactical aspects, it was found that both contained 12,% of total errors made by the students. For morphological aspects, it was found that only 3,1% of total errors was made. For the linguistic problems in phonological aspects, surprisingly it was found 0% of total errors . It can be concluded language acquisition of these students in the linguistic component of English as a foreign language was inadequate in the act of translating, especially in the level of